A delay in sampling information from temporally autocorrelated visual stimuli - Chloe Callahan-Flintoft (Nature Portfolio, 2020)
When a cue is provided, people can rapidly attend to a changing scene and remember how it looked right after the cue appeared, but if the scene changes gradually, there is a delay in what we remember. Here the authors model these effects as prolonged attentional engagement.